Poverty and depression among the urban poor in Malaysia: A narrative review - Rudi Nasib; Khamisah Awang Lukman; Pravina Deligannu; Nabihah Ali; Nachia Banu Abdul Rahim; Muhammad Mudassir Abdul Rahim; Nelson Lean Boon Leong (Universiti Putra Malaysia, 2023)
Malaysia has made significant progress in lowering poverty and improving most Malaysians’ living standards. Nevertheless, inequality is growing due to rapid urbanisation, particularly among low-income and poor urban families. Urbanisation and poverty have always been associated with detrimental effects on the mental health of the urban population. Hence, the review’s objective was to provide an overview of depression among the urban poor in Malaysia based on the most recent research. Approximately 23.9 to 57.8% of poor urban people in Malaysia were depressed. Household income, stressful events, younger age, loneliness, chronic health conditions, a lack of assets, and non-Malay ethnicity have all been linked to depression among Malaysia’s urban poor. Hence, the study revealed that depression is prevalent among Malaysia’s urban poor. There is an immediate need to address mental health issues among Malaysia’s urban poor.